Detection of Single‐feature Polymorphisms (SFPs) between two tomato varieties and their application in defining the introgressions of resistance loci. Issue 2 (22nd March 2015) - Milc, Justyna; Infantino, Alessandro; Aragona, Maria; Pecchioni, Nicola; Debener, T.
Abstract The objectives of the study were to (i) demonstrate that the hybridization data from microarrays can yield information on sequence variation between two inbred lines, an introgression line 'Mogeor' and its genetic background 'Moneymaker'; (ii) characterize, by means of the identified SFPs, the introgressed genomic segments of 'Mogeor', carrying resistance genes; and (iii) deliver a set of genetically anchored SFPs potentially useful for breeding. In this work, the GeSNP software was used to identify SFPs in tomato using Affymetrix data from a previous experiment. Sequencing of 12 putative polymorphism‐containing amplicons yielded a SFP probe set validation rate of 90%. In total, 92 Gene Models putatively harbouring SFPs were identified, distributed as following: 61 Gene Models on chromosome 9, and one to eight on the remaining tomato chromosomes apart from chromosomes 7, 8 and 12. Newly discovered SFPs from microarray data can thus provide not only useful information for definition of introgressed genomic regions, but also identification of candidate genes and new markers for MAS.